Pensión de alimentos: tendencia europea a las tablas - Javier Magán Arcones; Carolina Marín Pedreño (Revista Sobre la Infancia y la Adolescencia)
The calculation of child maintenance in Spain lacks guidance or criteria to assist in stabilizing the amount to pay.